The Influence of Individual Competence, Creativity, and Work Attitude on Lecturer Performance at the Faculty of Tarbiyah and Teacher Training - Roslaeni, Roslaeni; Wijaya, Candra; Syaukani, Syaukani (Fitrah: Journal of Islamic Education, 2025)
This study was motivated by the low effectiveness of lecturers’ performance, often influenced by their competence, creativity, and work attitudes at the Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Sumatera Utara. The study aimed to analyze the influence of individual competence and creativity on lecturers’ work attitudes and performance. Using a quantitative ex post facto approach, data were collected via questionnaires and analyzed inferentially. The results indicated that all hypotheses were supported: individual competence positively affected work attitudes by 17%, creativity contributed 21% to work attitudes, while competence and creativity influenced performance by 9.6% and 12%, respectively. Work attitudes also had a positive impact of 16% on performance. These findings highlight that enhancing competence, fostering creativity, and cultivating positive work attitudes are interrelated strategies essential for improving lecturers’ professionalism and the overall quality of higher education. The study implies the need for programs that strengthen competence, stimulate creativity, and nurture positive work attitudes to enhance teaching, research, and community service.